Recognizing the Stateless: A Dual-Narrative Reflection on Access to Higher Education through RPL for Refugees, Asylum Seekers, and Stateless People in South Africa (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2025)
This paper integrates a dual-narrative reflection and scoping review to explore how Recognition of Prior Learning (RPL) can be reconceptualised as a vehicle for equitable access to higher education for refugees, asylum seekers, and stateless persons in South Africa. Drawing on national, African, and global perspectives, the study critically examines the limitations of current inclusive RPL policy and practice. Although South Africa’s RPL framework is progressive in principle, its implementation excludes many displaced learners, particularly those with undocumented and informally acquired ecological knowledge and skills. Grounded in Fraser’s model of social justice, Freire’s pedagogy of the oppressed, environmental justice theory, decolonial ecopedagogy, and ethics of care, the paper identifies key systemic barriers and opportunities for reform. Using Arksey and O’Malley’s scoping review methodology alongside anonymised voices from displaced learners, the study proposes the RAPID-RPL model—Refugee Access Pathway through Inclusive, Decolonial RPL Design. This transformative framework integrates community ecological knowledge mapping, oral testimony, trauma-informed assessor training, multi-modal assessment, and policy coordination, aiming to dismantle exclusionary practices and foster epistemic justice. The proposed Green RPL Framework further aligns recognition with South Africa’s National Development Plan and Sustainable Development Goal 4 on Quality Education, advancing more inclusive, responsive, and sustainable pathways for displaced learners. Keywords: RPL, refugees, SDG 4, RAPID RPL, RPL policy, access, higher education